Community Empowerment Through Probiotic Production and Fish Feed Production Based on Local Materials in Gapoktan Mekar Mulyo, Sukun District, Malang City - Ganjar Adhywirwan Sutarjo; David Hermawan; Rahmad Pulung Sudibyo (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Increasing the local materials' utilization through community participation in freshwater fish farming is one of the keys to realizing family-based food independence. It can be done by utilizing narrow land, utilizing local raw materials that can be used as ingredients for handmade fish feed, preventing pests and diseases, and improving the aquatic environment's quality. Those steps need to get the attention of various parties through an appropriate technology approach. One of the areas for developing freshwater fish farming in Malang is the Sukun sub-district. The fish farmer group association called